Coming to terms with chance : engaging rational discrimination and cumulative disadvantage - Gandy Jr, Oscar H. (Ashgate, 2009)
The application of probability and statistics to an ever-widening number of life-decisions serves to reproduce, reinforce, and widen disparities in the quality of life that different groups of people can enjoy. As a critical technology assessment, the ways in which bad luck early in life increase the probability that hardship and loss will accumulate across the life course are illustrated. Analysis shows the ways in which individual decisions, informed by statistical models, shape the opportunities people face in both market and non-market environments. Ultimately, this book challenges the a.